Media And Communication: The Contestation Of 2024 Presidential Election Hoax News In Online And Social Media - Ikbal, Makpudin; Nuruzzaman, Nuruzzaman (Indonesian Journal of Multidisciplinary Science, 2025)
The spread of hoaxes (false news) during the 2024 presidential election has increased significantly compared to the 2019 presidential election. This phenomenon of political hoaxes not only deceives the public but is also used as a tool to attack political opponents, making the 2024 presidential election a battleground between presidential candidates. This study aims to uncover the content of political hoax news contestation during the 2024 presidential election. This study uses qualitative research with content analysis, which provides an overview of the rampant spread of political hoax news that can threaten the political stability of the country. This study also aims to increase public literacy and awareness of the dangers of hoax news and how to anticipate it. The results of the study show that social media, especially Facebook, is the main focus of hoax news dissemination. Political hoax news in the 2024 presidential election tends to appear in a chain-like manner and often reproduces information that has already circulated in the 2019 presidential election. The target of this hoax news contest is the 2024 presidential candidates. The strategy for spreading fake news is highly effective by leveraging social media and tends to incite hatred between groups. Therefore, this study recommends that the government actively educate the public about media literacy. As a result, all segments of society are expected to become more selective in receiving information.